Pristine Inner Experience and Descriptive Experience Sampling: Implications for Psychology - Lapping-Carr, Leiszle R.; Heavey, Christopher L. (Frontiers in Psychology, 2017)
Pristine inner experience is that which is directly present in awareness before it is distorted by attempts at observation or interpretation. Many psychological methods, including most introspective methods, attempt to measure some aspect of pristine inner experience (thoughts, feelings, mental imagery, sensations, etc.). We believe, however, that these methods produce unspecifiable combinations of pristine inner experience, beliefs about the self, beliefs about what inner experience should be like, inaccurate recollections, miscommunications, and other confounding influences. We argue that Descriptive Experience Sampling (DES) can produce high fidelity descriptions of pristine inner experience. These descriptions are used to create idiographic profiles, carefully crafted, in-depth characterizations of the pristine inner experience of individuals. We believe these profiles, because they are built from moments apprehended via a method that confronts the challenges inherent in examining inner experience, are uniquely valuable in advancing the science of inner experience and psychology broadly. For example, DES observations raise important questions about the veracity of results gathered via questionnaires and other introspective methods, like casual introspection. DES findings also provide high fidelity phenomenological data that can be useful for those developing psychological theories, such as theories of emotional processing. Additionally, DES procedures may allow clinicians and clients to practice valuable skills, like bracketing presuppositions and attending to internal experiences. This paper will describe difficulties inherent in the study of pristine inner experience and discuss implications of high fidelity descriptions of pristine inner experience for psychological research, theory development, and clinical practice.